Movement ecology of Afrotropical birds: Functional traits provide complementary insights to species identity - Habel,JC; Tobias,JA; Fischer,C (Biotropica, 2019)
Effects of anthropogenic activities on habitats and species communities and populations are complex and vary across species depending on their ecological traits. Movement ecology may provide important insights into species’ responses to habitat structures and quality. We investigated how movement behavior across a humanmodified landscape depends on species identity and species traits, with particular focus on habitat specialization, feeding guilds, and dispersal behavior. We tracked 34 individuals of nine Afrotropical bird species during three years in an anthropogenic riparian landscape of East Africa. We investigated whether species’ functional traits predicted their habitat use and movement behavior better than species’ identities. Our results indicate that habitat specialists mainly occur in dense riparian thickets, while habitat generalists do occur in agricultural land. Homeranges of omnivorous habitat generalists are larger than of frugivorous and insectivorous generalists and omnivorous and insectivorous specialists. Movement speed was highest in settlement areas for all species, with activity peaks during morning and afternoon for habitat specialists. Our results reveal that functional traits and species identity provide complementary insights into responses of organisms to habitat structures and habitat quality.